Activation of the ventral striatum during aversive contextual conditioning in humans - Pohlack, Sebastian; Nees, Frauke; Ruttorf, Michaela; Schad, Lothar R.; Flor, Herta (Biological psychology, 2012)
The goal of this study was to investigate the function of the ventral striatum and brain regions involved in anxiety and learning during aversive contextual conditioning. Functional magnetic resonance imaging was used to assess the hemodynamic brain response of 118 healthy volunteers during a differential fear conditioning paradigm. Concurrently obtained skin conductance responses and self-reports indicated successful context conditioning. Increased hemodynamic responses in the ventral striatum during presentation of the conditioned visual stimulus that predicted the aversive event (CS+) compared to a second stimulus never paired with the aversive event (CS−) were observed in the late acquisition phase. Additionally, we found significant brain responses in the amygdala, hippocampus, insula and medial prefrontal cortex. Our data suggest the involvement of the ventral striatum during contextual fear conditioning, and underline its role in the processing of salient stimuli in general, not only during reward processing.